Advanced Technique for License Plate Extraction - Prachi Upasani, Soojey Deshpande, Ashwini Suryavanshi, Nitin Gaikwad (Mathematical Statistician and Engineering Applications, 2022)
Automatic Number Plate Recognition (ANPR) is a mass reconnaissance tool that takes pictures of distant vehicles and reads their licence plates. In finding stolen vehicles, ANPR may be helpful. The ANPR systems installed on highways can be used to identify stolen vehicles in an efficient manner. The image of the vehicle plate is obtained by the digital cameras, and the image is then processed to extract the number plate data. Numerous algorithms are used to take and process a vehicle’s rear image.